2006
DOI: 10.2478/v10001-006-0033-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum Clara Cell Protein as an Indicator of Pulmonary Impairment in Occupational Exposure at Aluminum Foundry

Abstract: Objectives: Although some of the exposures in aluminum (Al) smelting have been well characterized, and respiratory disorders in aluminum production workers are well known, the relationship between internal aluminum loads and appropriate lung biomarkers have not been elucidated. The aim of our work was to carry out a comprehensive investigation in workers employed in the Aluminum Foundry Casting Department with special reference to currently existing hygiene standards, known as threshold limit values (TLV) base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 82 publications
(83 reference statements)
1
5
0
3
Order By: Relevance
“…Lowering CC16 serum level was one of the most sensitive, however not-specific biomarker in occupational exposure [8,9,13]. The relationship between low CC16 level in serum and abnormal results of the VEP brain function tests and concomitant high Al serum level may also indicate possibility of the interaction between Al in serum and transfer of protein originated from epithelial respiratory cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lowering CC16 serum level was one of the most sensitive, however not-specific biomarker in occupational exposure [8,9,13]. The relationship between low CC16 level in serum and abnormal results of the VEP brain function tests and concomitant high Al serum level may also indicate possibility of the interaction between Al in serum and transfer of protein originated from epithelial respiratory cells.…”
Section: Discussionmentioning
confidence: 97%
“…As a cell-specific marker for nonciliated bronchiolar epithelial Clara cells, which play a part in immunomodulatory and/or antiinflammatory processes, assessment of Clara cell protein in serum (CC16) was proposed by various authors [6,7]. Recent studies have shown that CC16 is a sensitive biomarker of respiratory epithelial injury in exposures of humans and animals to welder fumes [8], nitric oxides [9], glutaraldehyde [10], or low CC16 levels in serum were noted in active smokers [11,12] and in silicaexposed workers [13].…”
Section: Introductionmentioning
confidence: 99%
“…Las investigaciones muestran que el nivel de toxicidad del Al puede ser muy bajo (21) y puede provocar enfermedades respiratorias (4,16,21,22), neurológicas (15,17,23) y recientemente se ha reportado su efecto cancerígeno (24,25).…”
Section: Discussionunclassified
“…Los efectos respiratorios se han observado principalmente en trabajadores expuestos (4,5,26,27) y estudios experimentales indican que la presencia de Al se correlaciona con proceso inflamatorio pulmonar (22,28).…”
Section: Discussionunclassified
“…При этом у курящих больных асбестозом синтез СС16 был достоверно выше по сравнению со здоровыми курильщиками, но ниже, чем у некурящих больных, что дало возможность предложить СС16 в качестве биомаркера при проф заболеваниях как у курящих, так и некурящих [17,18]. Установлена обратная зависимость между кон центрациями СС16 и ионов алюминия в сыворотке крови у рабочих алюминиевой промышленнос ти [19]. Хроническое воздействие аллергенов вызы вает метаплазию булавчатых клеток, что приводит к снижению их защитных свойств и уровня СС16 в жидкости бронхоальвеолярного лаважа, при этом противовоспалительная терапия способствует вос становлению нормального фенотипа булавчатых клеток и их функций [20].…”
Section: оригинальные исследованияunclassified